Rencana Tata Ruang Kawasan Metropolitan Manado-Bitung - Windi, Windi; Aguswin, Ahmad; Gunawan, Alwan (Jurnal Pelita Teknologi, 2020)
The Manado-Bitung Metropolitan Area Plan aims to create an integrated and sustainable area by paying attention to economic, social and environmental growth. This study assesses the existing conditions and development potential in the area, identifies challenges, and formulates a comprehensive spatial planning strategy. The planning approach used involves analyzing factors such as transportation, infrastructure, land use, and socio-economic dynamics. The plan is designed to improve connectivity between Manado and Bitung, support industrial and tourism development, and promote environmentally friendly development. It is hoped that the implementation of this spatial planning plan can accelerate regional economic growth, reduce the disparity between regions, and improve the quality of life of the community. The conclusion of this study shows that integrated and participatory spatial planning is essential to achieve sustainable and inclusive metropolitan development.